2020
DOI: 10.46298/epiga.2020.volume4.5924
|View full text |Cite
|
Sign up to set email alerts
|

Remarks on the positivity of the cotangent bundle of a K3 surface

Abstract: Using recent results of Bayer-Macr\`i, we compute in many cases the pseudoeffective and nef cones of the projectivised cotangent bundle of a smooth projective K3 surface. We then use these results to construct explicit families of smooth curves on which the restriction of the cotangent bundle is not semistable (and hence not nef). In particular, this leads to a counterexample to a question of Campana-Peternell. Comment: Published version

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Statement (c) is a consequence of Lemma 3.1. For (d), this is already proved in [16, Section 4.2.2] for S$S$ being very general. On the other hand, note that ζ+32πH$\zeta +\frac{3}{2}\pi ^*H$ is nef only if ζ+(32+ε)πH$\zeta +(\frac{3}{2}+\varepsilon )\pi ^*H$ is ample for any real numbers ε>0$\varepsilon >0$.…”
Section: Del Pezzo Threefoldsmentioning
confidence: 54%
See 2 more Smart Citations
“…Statement (c) is a consequence of Lemma 3.1. For (d), this is already proved in [16, Section 4.2.2] for S$S$ being very general. On the other hand, note that ζ+32πH$\zeta +\frac{3}{2}\pi ^*H$ is nef only if ζ+(32+ε)πH$\zeta +(\frac{3}{2}+\varepsilon )\pi ^*H$ is ample for any real numbers ε>0$\varepsilon >0$.…”
Section: Del Pezzo Threefoldsmentioning
confidence: 54%
“…Proof Statement (a) is proved in [44, Proposition 2.3], [46, Proposition 3.14] and (b) follows from [16, Corollary 4.2]. Statement (c) is a consequence of Lemma 3.1.…”
Section: Del Pezzo Threefoldsmentioning
confidence: 87%
See 1 more Smart Citation
“…These K3 surfaces and their Hilbert squares are related to nodal cubic fourfolds and their Fano varieties cf. [Ha,4.2,Lemma 6.3.1], [DM,Example 6.4], [GO,4.3].…”
Section: The Heegner Divisor Dmentioning
confidence: 99%
“…The K3 surface S ⊂ P 4 is the complete intersection of a smooth quadric and a cubic hypersurface. Taking this quadric to be a hyperplane section of the Grassmannian Gr(2, 4) ⊂ P 5 , in [GO,Lemma 4.5] it is shown that the Mukai bundle V can be chosen to be the restriction of the dual of the universal bundle on Gr(2, 4) to S.…”
Section: The Heegner Divisor Dmentioning
confidence: 99%